Investigating the Efficacy and Experiences With Narrative Exposure Therapy in Severe Mentally Ill Patients With Comorbid Post-traumatic Stress Disorder Receiving Flexible Assertive Community Treatment: A Mixed Methods Study - Mauritz, Maria; Goossens, Peter; Jongedijk, Ruud; Vermeulen, Hester; van Gaal, Betsie (Frontiers in Psychiatry, 2022)
Background Severe mentally ill patients with interpersonal trauma and post-traumatic stress disorder have a negative illness course. Traumas are often not treated because of their vulnerability. Narrative Exposure Therapy is an effective trauma therapy. It is unknown whether this therapy is effective and tolerable in these patients receiving community mental health care. Objectives 1) To evaluate whether Narrative Exposure Therapy in severe mentally ill outpatients changes post-traumatic stress disorder, dissociation, psychiatric symptoms, care needs, quality of life, global functioning, and care consumption. 2) To gain insight how patients perceive this therapy. 3) To identify influencing factors on therapy results and to compare diagnostic changes with patient’s experiences. Design A convergent mixed methods design including a single group pre-test-post-test repeated-measures design and a Grounded Theory approach and thematic analysis. Participants Adult psychiatric outpatients (age 21-65) with post-traumatic stress disorder related to interpersonal trauma. Methods Baseline demographics and clinical characteristics were collected. Quantitative measures included post-traumatic stress disorder, dissociation, and psychiatric outcomes, which were assessed at pre-treatment (T0), one month post-treatment (T1), and seven months follow-up (T2). A linear mixed models was performed to analyze the course of illness. Qualitative data were collected three months after T1 using individual semi-structured in-depth interviews. The merged analysis compared quantitative and qualitative results for each participant. Results Twenty three outpatients (female 82%), mean age 49.9 years (SD 9.8) participated. The post-traumatic stress disorder score decreased from mean 37.9 at T0 to 31.9 at T1 (-6.0, 95%CI -10.0 to -2.0), and to 24.5 at T2 (-13.4, 95%CI -17.4 to -9.4). Dissociation, psychiatric symptoms, contacts, and medication decreased, global functioning increased; quality of life and perceived needs did not change. Qualitative analysis showed that participants experienced this therapy as intensive, but most tolerated it well. Afterwards, eighteen participants perceived less symptoms. Mixed analysis showed substantial congruency between quantitative scores and participants’ perception. Positive outcomes were related to sufficient support and vice versa. Conclusions Severe mentally ill outpatients experienced Narrative Exposure Therapy as intensive, but most of them tolerate it well. This therapy is clear efficacious in this group. Trial registration Trial NL5608 (NTR5714).